Synthesis of Thienopyrimidines and their Antipsychotic Activity - Chanchal Sharma; Swapnil Yerande; Rajashree Chavan; A. V. Bhosale (E-Journal of Chemistry)
A series of thienopyrimidines and related heterocycles were synthesized by refluxing related imidoyl chloride with primary and secondary amines under microwave irradiation and classical heating. The imidoyl chlorides were synthesized from corresponding cyclic imides with phosphorus oxychlorides under microwave irradiation and classical heating. The structures of the compounds were confirmed by FT-IR, NMR. The synthesized compounds were screened for anti psychotic activity.